How is the adoption of advances of ICT valued by the market through the Tobin’s Q indicator? The case of Vietnamese commercial banks - Phuc, Nguyen, Tran; Thu, Le Thi Anh (The Economics and Finance Letters, 2025)
This study aims to examine the impact of information and communication technology (ICT) investment on the market-based performance of Vietnamese commercial banks. Using panel data from 26 banks over the period 2006–2022, the research adopts the system generalized method of moments (System-GMM) to address potential endogeneity and dynamic panel bias. ICT investment is measured through a composite ICT index, while performance is captured by Tobin’s Q, a market-based indicator reflecting investor expectations. The findings reveal that ICT investment has a positive and significant effect on Tobin’s Q, underscoring the strategic role of technology in enhancing a bank’s market valuation. In addition to ICT, factors such as bank size, the loan-to-deposit ratio, the loan loss provision ratio, and macroeconomic conditions are also found to significantly influence Tobin’s Q in ways consistent with prevailing banking practices and the economic context during the study period. The study concludes that ICT investment plays a strategic role in improving market-based performance and signaling future value to investors. These findings suggest that Vietnamese banks should adopt long-term, strategic ICT investment plans not only to enhance competitiveness but also to support broader goals of innovation and digital transformation in the banking sector, particularly in the context of Industry 4.0.